P427 One Year Follow up of Three Phase IB/IIA Clinical Trials of Ex Vivo Expanded Allogeneic Bone Marrow Derived Mesenchymal Stem Cells for the Treatment of Fistulizing Crohn's Disease. (30th January 2023) - Lightner, A; Otero Pineiro, A; Reese, J; Ream, J; Nachand, D; Obi, M; Adams, A; VanDenBossche, A; Dadgar, N; Hull, T
Abstract: Background: Mesenchymal stem cells (MSCs) have been used for the treatment of perianal Crohn's fistulizing disease by direction injection. However, to date, studies have excluded patients with proctitis, anal canal involvement, vaginal involvement, and an ileal pouch in situ. We sought to assess the safety and efficacy of a direct injection of MSCs for the treatment of perianal, rectovaginal, and peripouch Crohn's fistula(s). Methods: Three phase IB/IIA randomized control trials of perianal (n=23), rectovaginal (n=19) and peripouch (n=22) Crohn's related fistulas were conducted to determine safety and efficacy of MSCs for refractory phenotypes of perianal Crohn's disease. Crohn's patients with perianal, rectovaginal, and peripouch Crohn's fistulizing disease were offered enrollment into a clinical trial. A total of 75 million MSCs were administered with a 22G needle by direct injection after curettage and primary closure of the fistula tract. A repeat injection of 75 million MSCs was administered at 3 months if complete clinical and radiographic healing were not achieved. Adverse and serious adverse events were collected at post procedure day 1, week 2, week 6, month 3, month 6 and month 12. Clinical healing, radiographic healing per magnetic resonance imaging, and patient reported outcomes were assessed at the same time points. Results: A total of 64 patients were enrolled and treated; 49 were treatment and 15 were control. There were no adverse or serious adverse events reported related to investigational product. At twelve months, overall combined clinical and radiographic healing was achieved in 70% of perianal, 37.5% of rectovaginal, and 46.2% of ileal pouch fistulas, respectfully. In the control cohorts, 12 month healing was 0%, 0%, and 0% in the three clincial trials respectively. The perianal Crohn's disease activity index and VanAssche score all significantly decreased in treatment patients at six and twelve months, but not in the control groups. Conclusion: Allogeneic bone marrow derived MSCs offer a safe and effective alternative treatment approach for severe phenotypes of perianal fistulizing Crohn's disease.